Aktivitas Antioksidan Ekstrak Etanol Daun Kelapa Sawit (Elaeis guineensis Jacq.): Antioxidant Activity of Oil Palm Leaf Ethanol Extract (Elaeis guineensis Jacq.) - Masrurotin Zumaro; Hifdzur Rashif Rija’i; Angga Cipta Narsa; Riski Sulistiarini; Helmi Helmi (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Indonesia is a country with abundant natural wealth and almost all types of plants can grow in the territory of this country. One of them is oil palm leaf (Elaeis guineenis Jacq.) containing terpenoid compounds, steroids, alkaloids, flavonoids, glycosides, tannins and saponins and also this plant among the community has benefits that can be used for the treatment of skin infections. Purpose of this study was to determine the yield obtained as well as the antioxidant activity of ethanol extract of oil palm leaves. Oil palm leaves were extracted using 96% ethanol as solvents and using the maceration method. Testing the antioxidant activity of the ethanol extract of oil palm leaves was carried out using the DPPH method (2,2-diphenyl-1-picrylhydrazyl), where the absorbance was measured at max 515 nm using a UV-vis spectrophotometer. The results showed that the yield of oil palm leaf ethanol extract obtained as much as 5.44 % and obtained that the ethanolic extract of oil palm leaves had antioxidant activity against DPPH radicals with an IC50 value of 133.58 ppm. It could be concluded that the ethanolic extract of oil palm leaves (Elaeis guineensis Jacq.) had antioxidant activity in the moderate category because the IC50 value was between 100- 150 ppm.